Paparan Konten Potongan Film di Instagram @netflixid terhadap Keputusan Menonton Mahasiswa Komunikasi Digital Media - Salsabila Maharani; Wahyu Budi Priatna; Leonard Dharmawan (Bahasa Indonesia, 2026)
The development of digital technology has transformed how people consume media, particularly within the entertainment industry. Social media, especially Instagram, has become an influential platform for film promotion due to its strong visual appeal and interactive nature. This research aims to analyze the influence of exposure to film clip content on the official Instagram account @Netflixid toward students’ viewing decisions in the Digital Communication and Media Study Program at IPB Vocational School. The study is grounded in the Uses and Effect Theory and the AIDA Model, which explain how media messages and audience engagement interact to produce behavioral effects. A quantitative explanatory method was employed, using a questionnaire distributed online to 75 respondents. The collected data were analyzed using validity, reliability, and simple linear regression tests through SPSS version 29. The findings indicate that exposure to film clip content on @netflixid has a positive and significant effect on students’ viewing decisions. The results confirm that Instagram-based promotional strategies can effectively influence audience behavior and highlight the continuing relevance of media exposure and persuasion theories in digital communication studies.